Rheumatic?—A Digital Diagnostic Decision Support Tool for Individuals Suspecting Rheumatic Diseases: A Multicenter Pilot Validation Study - Knevel, Rachel; Knitza, Johannes; Hensvold, Aase; Circiumaru, Alexandra; Bruce, Tor; Evans, Sebastian; Maarseveen, Tjardo; Maurits, Marc; Beaart-van de Voorde, Liesbeth; Simon, David; Kleyer, Arnd; Johannesson, Martina; et al. (Frontiers in Medicine, 2022)
Introduction: Digital diagnostic decision support tools promise to accelerate diagnosis and increase health care efficiency in rheumatology. Rheumatic? is an online tool developed by patients and specialists in rheumatology and general medicine. It calculates a risk score for several rheumatic diseases. We ran pilot study retrospectively testing Rheumatic? for its ability to differentiate symptoms from existing or emerging immune-mediated rheumatic diseases from other rheumatic and musculoskeletal complaints and disorders in patients visiting rheumatology clinics. Materials and Methods: The performance of Rheumatic? was tested in three rheumatology centers: A) patients at Risk for RA (Karolinska Institutet, n=50 individuals with musculoskeletal complaints and anti-citrullinated protein antibody positivity) (B) patients with joint swelling (Erlangen, n=52). (C) patients with early arthritis where the clinician considered it likely to be of auto-immune origin (Leiden, n=73). In dataset A, we tested whether Rheumatic? could predict the development of arthritis. In dataset B and C we tested whether Rheumatic? could predict the development of an immune-mediated rheumatic diseases. We examined the discriminative power of the total score with the Wilcoxon rank test and the area-under-the-receiver-operating-characteristic curve (AUC-ROC). Next, we calculated the test characteristics for patients passing the first or second Rheumatic? scoring threshold (advising to visit primary or secondary care doctor). Results: The total testscores differentiated: (A) Individuals developing arthritis or not, median 245vs163, P < 0.0001, AUC-ROC = 75.3; (B) patients with an immune-mediated arthritic disease or not, median 191vs107, P < 0.0001, AUC-ROC = 79.0,; but less well patients with an immune-mediated arthritic disease or not amongst those where the clinician already considered an immune mediated disease most likely (median 262vs212, P < 0.0001, AUC-ROC = 53.6. Threshold-1 was highly specific in dataset A and B (0.72, 0.87 and 0.23, respectively) and sensitive (0.67, 0.61 and 0.67) . Threshold-2 was very specific in all three centers but not very sensitive: specificity of 1.0, 0.96 and 0.91, sensitivity 0.05, 0.07, 0.14 in dataset A, B and C respectively. Conclusion: Rheumatic? is a web-based patient-centered multilingual diagnostic tool capable of differentiating immune-mediated rheumatic conditions from other musculoskeletal problems. The current scoring system needs to be further optimized.